2022
DOI: 10.1021/acs.nanolett.1c04624
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Metal Halides to Facet-Modulated Lead Halide Perovskite Platelet Nanostructures on A-Site Cs-Sublattice Platform

Abstract: The conversion of metal halides to lead halide perovskites with B-site metal ion diffusion has remained a convenient approach for obtaining shape-modulated perovskite nanocrystals. These transformations are typically observed for materials having a common A-site Cs-sublattice platform. However, due to the fast reactions, trapping the interconversion process has been difficult. In an exploration of the tetragonal phase of Cs7Cd3Br13 platelets as the parent material, herein, a slower diffusion of Pb­(II) leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 55 publications
0
15
1
Order By: Relevance
“…Hence, understanding facet chemistry and facet dependent anisotropic growth leading to shape modulations could not be largely understood. Literature reports revealed that modifying surfaces and using specific ligands, cubes, multifaceted polyhedrons, platelets, and rods/wires of these nanocrystals could be designed. , However, these shapes are limited and need further exploration. Moreover, for the ionic nature and fast formation of these nanocrystals, shape modulation following a classical approach remained indeed difficult.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, understanding facet chemistry and facet dependent anisotropic growth leading to shape modulations could not be largely understood. Literature reports revealed that modifying surfaces and using specific ligands, cubes, multifaceted polyhedrons, platelets, and rods/wires of these nanocrystals could be designed. , However, these shapes are limited and need further exploration. Moreover, for the ionic nature and fast formation of these nanocrystals, shape modulation following a classical approach remained indeed difficult.…”
mentioning
confidence: 99%
“…These reactions were very fast, and hence, decoupling steps to understand the exact growth process remained indeed difficult. Literature reports revealed that Cd­(II) has been extensively used for the synthesis of different perovskite nanostructures, ,,, but in either case, no such cube coupled star nanocrystals were reported. However, it is also established that the formation of an intermediate heterostructure such as CsPbBr 3 –Cs 2 CdBr 4 and CsPbBr 3 –Cs 7 Cd 3 Br 13 is possible during shape conversion. , This provided the initial impression of heterostructure induced secondary nucleations leading to cube coupled star nanocrystals.…”
mentioning
confidence: 99%
“…In addition to multijunctions, in most cases, these were observed to be hollow at the center. This was expected due to incomplete ion replacement and the elimination of the host part of the parent nanocrystals at the center during annealing . More representative TEM and HRTEM images of these multijunction CsPbBr 3 disc nanocrystals having more than four junctions are shown in Figures S16–S18.…”
Section: Resultsmentioning
confidence: 98%
“…In either case, the Cs-sublattice structure remains common, and as Cs is larger in size, the lattice structures are expected to be rigid during this ion exchange process. There are several such reports on Cs-sublattice structures which helped in interconversions between metal halides and lead halide perovskite crystals. , Hence, in this case also the Cs-sublattice structure determined the pathways of such unique 2D-shaped nanostructure formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation